1998
DOI: 10.1002/(sici)1096-9071(199806)55:2<147::aid-jmv11>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A survey for 32 nucleotide deletion in the CCR-5 chemokine receptor gene (Δccr-5) conferring resistance to human immunodeficiency virus type 1 in different ethnic groups and in chimpanzees

Abstract: The 32 nucleotide deletion in the CCR-5 chemokine receptor gene referred to as deltaccr-5 has been shown to confer resistance to HIV-1. Using PCR, 1,105 human subjects and 33 common chimpanzees were genotyped attributing them to one of the three possible genotypes: wild-type homozygote (w/w); deltaccr-5 homozygote (deltaccr-5/deltaccr-5) and deltaccr-5/wild-type heterozygotes (deltaccr-5/w). The ethnic groups investigated included different Middle Eastern nationalities (mainly Arab) and Russians. Carriers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The CCR5D32 allele frequency found in this study was similar to the frequencies previously reported for Russia. It is interesting to note that the closest figures were found previously in Moscow (0.095, x 2 5 0.31, p 5 0.57) (Kazennova et al, 1998), whereas the frequencies for other regions of Russia were higher (range, 0.11-0.13) (Aseev et al, 1997;Slominskii et al, 1997;Voevodin et al, 1998;Yudin et al, 1998). This could be due to higher proportion of FinnoUgrian population, characterized by high frequency of this allele (Pastinen et al, 1998), in the cohorts from those studies.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The CCR5D32 allele frequency found in this study was similar to the frequencies previously reported for Russia. It is interesting to note that the closest figures were found previously in Moscow (0.095, x 2 5 0.31, p 5 0.57) (Kazennova et al, 1998), whereas the frequencies for other regions of Russia were higher (range, 0.11-0.13) (Aseev et al, 1997;Slominskii et al, 1997;Voevodin et al, 1998;Yudin et al, 1998). This could be due to higher proportion of FinnoUgrian population, characterized by high frequency of this allele (Pastinen et al, 1998), in the cohorts from those studies.…”
Section: Resultssupporting
confidence: 60%
“…At the same time, limited information concerning only the CCR5D32 distribution in several regions of the Russian Federation is currently available (Aseev et al, 1997;Slominskii et al, 1997;Kazennova et al, 1998;Voevodin et al, 1998;Yudin et al, 1998). The aim of this study was (1) to determine the distribution of CCR5D32, CCR5-59029A/G, CCR2-64I, and SDF1-39A alleles among a representative sample of the Moscow population and (2) to estimate the co-occurrence or genotypic independence of those alleles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the reported prevalence of CCR5-D32 is < 1% in Syria and was absent in Lebanon. 5,18,19 In countries such as Bahrain, Iraq, Kuwait, and Saudi Arabia, the prevalence is approximately equivalent with a distribution of CCR5-D32 between 2% and 3%. 5 The results of the current study showed that the frequency of CCR5-D32 in Jordan is 0.6%.…”
mentioning
confidence: 99%
“…Low frequencies have been observed among Kuwaitis, Syrians, and Egyptians from Ismailia (1%, b1%, 0.6%, and 0.5%, respectively) (Salem and Batzer, 2007;Voevodin et al, 1998). This allele was expected to be completely absent among Egyptians from the Sinai, Sudanese and Yamanis (Martinson et al, 1997;Salem and Batzer, 2007;Voevodin et al, 1998). These findings might not reflect the real frequency of this deletion among the studied populations due to the small size of samples (b 100).…”
Section: Discussionmentioning
confidence: 85%
“…Within Middle East region, the frequency was found to be 2.8% among Bahrainis, followed by 2.5%, 2.4%, 2.1%, and 0.6% in Lebanese, Iranians, Saudis, and Jordanians, respectively (Gharagozloo et al, 2005;Karam et al, 2004;Khabour et al, 2013;Martinson et al, 1997;Salem et al, 2009;Stephens et al, 1998). Low frequencies have been observed among Kuwaitis, Syrians, and Egyptians from Ismailia (1%, b1%, 0.6%, and 0.5%, respectively) (Salem and Batzer, 2007;Voevodin et al, 1998). This allele was expected to be completely absent among Egyptians from the Sinai, Sudanese and Yamanis (Martinson et al, 1997;Salem and Batzer, 2007;Voevodin et al, 1998).…”
Section: Discussionmentioning
confidence: 96%